2023
DOI: 10.3390/su152215857
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Visual Relationship between Function and Facade in Historic Buildings Using Deep Learning—A Case Study of the Chinese Eastern Railway

Peilun Li,
Zhiqing Zhao,
Bocheng Zhang
et al.

Abstract: Although functional identifiability represents a key aspect for promoting visual connotation and sustainable usability in historic building groups, there is still no consensus on how to quantitatively describe its identification basis at a large scale. The recent emergence of the potentiality of deep learning and computer vision has provided an alternative to traditional empirical-based judgment, which is limited by its subjective bias and high traversal costs. To address these challenges, this study aims to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…However, the GVI has been employed in most of the current studies to assess a single city [32,33], and less is known about the GVI with regard to regional areas of special interest. Areas covered by the CER network have been mapped to analyze the spatial distributions of different types of urban infrastructures [3,5]. This supports the idea that regional distributions of landscape surface functions can be characterized by patterns framed with distances to railway lines and landscape metrics.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…However, the GVI has been employed in most of the current studies to assess a single city [32,33], and less is known about the GVI with regard to regional areas of special interest. Areas covered by the CER network have been mapped to analyze the spatial distributions of different types of urban infrastructures [3,5]. This supports the idea that regional distributions of landscape surface functions can be characterized by patterns framed with distances to railway lines and landscape metrics.…”
Section: Introductionsupporting
confidence: 57%
“…A recent study revealed that industrial parks are a type of urban infrastructure that attracts urban planning with vegetation, maintaining a GVI of over 20%. The functions of old infrastructure in cities near CER lines were mainly intended for civil uses, such as business, medicine, education, and religion, among others [5]. There has been little evidence demonstrating the establishment of industrial parks in regions near CER routes.…”
Section: Attributes Of Gvi In Urban Parks Distributed Along Cer Routesmentioning
confidence: 99%
See 2 more Smart Citations